The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/ncomms11277
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone receptor signalling in osterix-expressing mesenchymal progenitors is essential for tooth root formation

Abstract: Dental root formation is a dynamic process in which mesenchymal cells migrate toward the site of the future root, differentiate and secrete dentin and cementum. However, the identities of dental mesenchymal progenitors are largely unknown. Here we show that cells expressing osterix are mesenchymal progenitors contributing to all relevant cell types during morphogenesis. The majority of cells expressing parathyroid hormone-related peptide (PTHrP) are in the dental follicle and on the root surface, and deletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
138
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(146 citation statements)
references
References 46 publications
(55 reference statements)
3
138
0
5
Order By: Relevance
“…Previous studies have indicated that CNC-derived cells contribute to mesenchymal tissues during early development (Chai et al, 2000), although there have been limited studies using genetic cell lineage tracing to demonstrate the dynamic contribution of CNC-derived cells specifically during root formation. Recently, however, using an inducible Cre line, researchers have found that osterix (Sp7)-positive mesenchymal cells contain progenitor cells that contribute to different mesenchymal cell types during root development (Ono et al, 2016). We have also recently generated a Pax9-CreER line that can specifically target the CNC-derived mesenchyme in order to follow its contribution to different mesenchymal cell types during root formation (Feng et al, 2016).…”
Section: Box 1 Glossarymentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have indicated that CNC-derived cells contribute to mesenchymal tissues during early development (Chai et al, 2000), although there have been limited studies using genetic cell lineage tracing to demonstrate the dynamic contribution of CNC-derived cells specifically during root formation. Recently, however, using an inducible Cre line, researchers have found that osterix (Sp7)-positive mesenchymal cells contain progenitor cells that contribute to different mesenchymal cell types during root development (Ono et al, 2016). We have also recently generated a Pax9-CreER line that can specifically target the CNC-derived mesenchyme in order to follow its contribution to different mesenchymal cell types during root formation (Feng et al, 2016).…”
Section: Box 1 Glossarymentioning
confidence: 99%
“…For example, Bmp, Tgfβ, and their mediator Smad4, as well as Shh, Msx2 and Dlx2, are expressed in HERS cells (Åberg et al, 1997;Huang et al, 2010;Lezot et al, 2000;Nakatomi et al, 2006;Yamashiro et al, 2003). In the CNC-derived dental mesenchyme adjacent to the HERS, there is expression of Gli1, Nfic, Fgf, Tgfβ, Bmp, Wnt and its inhibitors, as well as PTHrP/PPR (Pthlh/Pth1r) (Huang et al, 2010;Ono et al, 2016;Steele-Perkins et al, 2003;Wang et al, 2013). In addition, some signaling molecules are expressed in both the HERS and the CNC-derived dental mesenchyme .…”
Section: Signaling Network That Regulate Tooth Root Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of posttranslation processing, PTHrP could generate a variety of fragments, including PTHrP (1–34), PTHrP(38–94), and PTHrP (107–139) peptide (Mangin et al, ; Thiede, Strewler, Nissenson, Rosenblatt, & Rodan, ). N‐terminal PTHrP (1–34) plays an important role in tooth and bone development (Ono et al, ). Mid‐region PTHrP (38–94) affects the placental calcium transport (Kovacs et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Osx potentially marks dental mesenchymal progenitors that differentiate into odontoblasts and produce mineralized dentin matrix . We noticed that conditional disruption of Bmpr1a using a constitutively active Osx‐Cre results in embryonic lethality (data not shown) and thus we decided to use an inducible (Tet‐off) system to activate Cre activity during postnatal development.…”
Section: Resultsmentioning
confidence: 99%